The Effect of Good Corporate Governance and Financial Performance on Tax Aggressiveness in Processed Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange 2020-2024 - Salsa Zuhrufa Sheila; Dewi Pudji Rahayu; Farah Nisa Ul Albab; Rakan Agi Musyaffa (IECON: International Economics and Business Conference, 2025)
This study seeks to examine the influence of institutional ownership, interpreted as an indicator of Good Corporate Governance (GCG) and financial performance, evaluated through measures of profitability and leverage, influence the practice of tax aggressiveness among firms within the Processed Food & Beverage Subsector that are recorded on the Indonesia Stock Exchange for the period 2020-2024. Adpoting a quantitative research framework, yhe investigation applies multiple linear regression analysis with the assistance of SPSS version 27. The sample was selected through a purposive sampling method, producing a total of 124 observations drawn from 39 corporate entities. The empirical results reveal that profitability significantly influences tax aggressiveness. In contrast, institutional ownership and leverage do not exhibit a meaningful impact. However, when considered together, all three variables show a significant combined influence on tax aggressiveness. Nonetheless, the Adjusted R² value of 17.7% suggests that the majority of the variation in tax aggressiveness is attributable to factors outside the scope of the present model. Overall, the findings highlight financial performance as a key element in managing corporate tax aggressiveness.